Digital Networks, Digital Pub(L)Ics (1): Labour, Pleasure, Porn. - Paasonen, Susanna; Albury, Kath; Stardust, Zahra; Mercer, John; Mowlabocus, Sharif; Robards, Brady; Smith, Clarissa (AoIR Selected Papers of Internet Research, 2017)
The Digital Networks, Digital Pub(l)ics panels (two panels in total) develop a critical conversation around the themes of intimacy, sexuality and embodiment and explore the ways in which these concepts are experienced, invoked and interrogated by different groups, communities and individuals in digital contexts. Speaking to the theme of the 2017 conference, the papers collectively identify, map and seek to understand the formation of publics constituted through the paradigms and practices of gender and sexuality. In this panel, scholars come together to explore the manifold ways in which pornography, historically framed as a ‘private concern’, has become a ‘public object’ in the digital age, around which new publics have formed. The shifting forms of digital porn production, involving new pornographic styles and new methods of framing pornographic texts, require us to (re)consider the political-economy of pornography and the ways in which publics produce, access and consume pornography. Papers one and two directly address pornography at the point of production. Complimenting this focus, papers three, four and five explore practices of porn consumption, once more attending to themes of labour, while also engaging with the notion of ’porn publics’. Together, these papers offer a series of critical interventions that signpost both the collaborative aspects of digital pornography and the challenges that the current political-economy of digital culture poses to notions of sexual freedom, sexual democracy and sexual publics.